Molecular dynamics study of model SI clathrate hydrates: the effect of guest size and guest-water interaction on decomposition kinetics - Das, Subhadip; Baghel, Vikesh Singh; Roy, Sudip; Kumar, Rajnish (Physical Chemistry Chemical Physics, 2015)
One of the options suggested for methane recovery from natural gas hydrates is molecular replacement of methane by suitable guests like CO2 and N-2. This approach has been found to be feasible through many experimental and molecular dynamics simulation studies. However, the long term stability of the resultant hydrate needs to be evaluated; the decomposition rate of these hydrates is expected to depend on the interaction between these guest and water molecules. In this work, molecular dynamics simulation has been performed to illustrate the effect of guest molecules with different sizes and interaction strengths with water on structure I (SI) hydrate decomposition and hence the stability. The van der Waals interaction between water of hydrate cages and guest molecules is defined by Lennard Jones potential parameters. A wide range of parameter spaces has been scanned by changing the guest molecules in the SI hydrate, which acts as a model gas for occupying the small and large cages of the SI hydrate. All atomistic simulation results show that the stability of the hydrate is sensitive to the size and interaction of the guest molecules with hydrate water. The increase in the interaction of guest molecules with water stabilizes the hydrate, which in turn shows a slower rate of hydrate decomposition. Similarly guest molecules with a reasonably small (similar to Helium) or large size increase the decomposition rate. The results were also analyzed by calculating the structural order parameter to understand the dynamics of crystal structure and correlated with the release rate of guest molecules from the solid hydrate phase. The results have been explained based on the calculation of potential energies felt by guest molecules in amorphous water, hydrate bulk and hydrate-water interface regions.

Molecular dynamics study on growth of carbon dioxide and methane hydrate from a seed crystal - Nakate, Prajakta; Ghosh, Bappa; Das, Subhadip; Roy, Sudip; Kumar, Rajnish (Chinese Journal of Chemical Engineering, 2019)
In the current work, molecular dynamics simulation is employed to understand the intrinsic growth of carbon dioxide and methane hydrate starting from a seed crystal of methane and carbon dioxide respectively. This comparison was carried out because it has relevance to the recovery of methane gas from natural gas hydrate reservoirs by simultaneously sequestering a greenhouse gas like CO2. The seed crystal of carbon dioxide and methane hydrate was allowed to grow from a super-saturated mixture of carbon dioxide or methane molecules in water respectively. Two different concentrations (1:6 and 1:8.5) of CO2/CH4 molecules per water molecule were chosen based on gas-water composition in hydrate phase. The molecular level growth as a function of time was investigated by all atomistic molecular dynamics simulation under suitable temperature and pressure range which was well above the hydrate stability zone to ensure significantly faster growth kinetics. The concentration of CO2 molecules in water played a significant role in growth kinetics, and it was observed that maximizing the CO2 concentration in the aqueous phase may not result in faster growth of CO2 hydrate. On the contrary, methane hydrate growth was independent of methane molecule concentration in the aqueous phase. We have validated our results by performing experimental work on carbon dioxide hydrate where it was seen that under conditions appropriate for liquid CO2, the growth for carbon dioxide hydrate was very slow in the beginning. (C) 2019 The Chemical Industry and Engineering Society of China, and Chemical Industry Press Co., Ltd. All rights reserved.
Keywords: Cage dynamics; CH4 recovery; CO2 sequestration; F-4 order parameter; kinetics; Natural gas hydrate; Thermodynamics